Neurofeedback Training of Gamma Oscillations in Monkey Primary Visual Cortex. (23rd February 2019) - Chauvière, L; Singer, W
Abstract: In humans, neurofeedback (NFB) training has been used extensively and successfully to manipulate brain activity. Feedback signals were derived from EEG, fMRI, MEG, and intracranial recordings and modifications were obtained of the BOLD signal, of the power of oscillatory activity in distinct frequency bands and of single unit activity. The purpose of the present study was to examine whether neuronal activity could also be controlled by NFB in early sensory cortices whose activity is thought to be influenced mainly by sensory input rather than volitional control. We trained 2 macaque monkeys to enhance narrow band gamma oscillations in the primary visual cortex by providing them with an acoustic signal that reflected the power of gamma oscillations in a preselected band and rewarding increases of the feedback signal. Oscillations were assessed from local field potentials recorded with chronically implanted microelectrodes. Both monkeys succeeded to raise gamma activity in the absence of visual stimulation in the selected frequency band and at the site from which the NFB signal was derived. This suggests that top–down signals are not confined to just modulate stimulus induced responses but can actually drive or facilitate the gamma generating microcircuits even in a primary sensory area.